Agro-development in Musali by using Muzara'ah supply chain model - Nayeem, M.M. (Serials Publications, 2017)
In the recent years many microfinance institutions have played significant role in banking and financial sector in Musali-Sri Lanka. Musali is divisional secretariat that situated in Mannar, a northern district of Sri Lanka. The study focused on domestic sector considerably paddy cultivation in this division. In order to enhance the agricultural financing and its productivity, Muzara'ah supply chain model was proposed. The aim of this paper is to investigate Muzara'ah supply chain model to overcome the financing problem in Musali. The analysis consists of various demographic variables and four factors such as benefits, prospects, challenges and implementation. The analysis used ANOVA, where the differences between groups could be identified. The study found that most of the government employees are satisfied with Muzara'ah supply chain model in terms of its prospect and benefits to the society. The model has features of risk diversification and investment. Therefore, financial institutions and farmers gain the benefits. © 2017 Serials Publications Pvt. Ltd.